Survey Research: process and limitations. - CRONIN, PATRICIA; RYAN, FRANCES; COUGHLAN, MICHAEL (My University, 2009)
Background: Survey research is a non-experimental research approach used to gather information about the incidence and distribution of, and the relationships that exist between, variables in a pre-determined population. Its uses include the gathering of data related to attitudes, behaviours and the incidence of events. For most modern researchers sample surveys are more cost effective and easier to undertake than population surveys when gathering information; however, this increases the risk of both representation and measurement errors. Contents: There are a number of different forms of survey research; however, they all share common steps and common limitations. This article discusses these steps with a view to highlighting some of the common difficulties. Conclusions: In the modern era, pressures on time and cost have led population census to, generally, be replaced by sample surveys. Newer survey methods of data collection may also help in reducing cost, but still have limitations. Researchers need to be aware of the potential errors that can occur with surveys, in order to reduce the risk in those areas that they can control.
PUBLISHED
Keywords: Nursing Education